Penerapan Metode Overall Equipment Effectiveness (OEE) dan Six Big Losses untuk Mengukur Efektivitas Mesin Packing pada PT. Surya Tsabat Mandiri - Rizqi Wahyudi; Rafi Gredita Ferdana; Andhyka Tyaz Nugraha (Universitas Teuku Umar, 2023)
This research aims to investigate the risk of six big losses and the effectiveness of packing machines at PT Surya Tsabat Mandiri in South Lampung using monthly data on production of bread products from March 2021 to February 2022 used in the research. Research was carried out on packing machine objects using quantitative data or data that can be measured systematically. The Overall Equipment Effectiveness (OEE) method is applied to measure the total performance of equipment as a whole according to what must be done and to assess the dominant factors of the Six Big Losses which are dominantly used by the fishbone diagram approach. The research results show that the average OEE value of packing machines is 78.17% and is still below world standards (≥85%). Apart from that, evidence was found that the most dominant six big losses factors were idling and minor stoppage losses with a value of 16.85% and reduced speed losses with a value of 7.85%. Based on the fishbone diagram, the aspects that cause speed losses on packing machines are humans (lack of operator knowledge, lack of workers guarding bread baskets), machines (repair of damaged machines, unstable center and end seal temperatures), environment (unstable production room temperature) and method (non-periodic machine maintenance). The recommendation given to reduce these two losses is to use the TPM pillars, namely education and training, autonomous maintenance and planned maintenance.